AlGaN/GaN high-electron-mobility transistor technology for high-voltage and low-on-resistance operation. (10th June 2016) - Kuzuhara, Masaaki; Asubar, Joel T.; Tokuda, Hirokuni
Abstract: In this paper, we give an overview of the recent progress in GaN-based high-electron-mobility transistors (HEMTs) developed for mainstream acceptance in the power electronics field. The comprehensive investigation of AlGaN/GaN HEMTs fabricated on a free-standing semi-insulating GaN substrate reveals that an extracted effective lateral breakdown field of approximately 1 MV/cm is likely limited by the premature device breakdown originating from the insufficient structural and electrical quality of GaN buffer layers and/or the GaN substrate itself. The effective lateral breakdown field is increased to 2 MV/cm by using a highly resistive GaN substrate achieved by heavy Fe doping. Various issues relevant to current collapse are also discussed in the latter half of this paper, where a more pronounced reduction in current collapse is achieved by combining two different schemes (i.e., a prepassivation oxygen plasma treatment and a field plate structure) for intensifying the mitigating effect against current collapse. Finally, a novel approach to suppress current collapse is presented by introducing a three-dimensional field plate (3DFP) in AlGaN/GaN HEMTs, and its possibility of realizing true collapse-free operation is described.